2006
DOI: 10.2174/156652306778520683
|View full text |Cite
|
Sign up to set email alerts
|

The Role of IRF1 and IRF2 Transcription Factors in Leukaemogenesis

Abstract: Acute myeloid leukaemia (AML) is the most common form of leukaemia in adults. Although of the order of 75-85% of patients will achieve complete remission after induction chemotherapy, long-term survival is still relatively low. Despite the progress in the rational design of drugs in disorders such as chronic myeloid leukaemia, AML lacks a single specific pathogenomic event to act as a drug target. Interferon regulatory factor 1 (IRF1) is a member of a family of related proteins that act as transcriptional acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 48 publications
2
17
0
1
Order By: Relevance
“…IRF1 mediates anti-proliferative and pro-apoptotic effects in cancer cells in a context-dependent and cell-type-specific manner (Choo et al, 2006). In the absence of antagonistic regulatory factors, increased expression and activation of IRF1 inhibits the expression of pro-survival members of the BCL2 family and simultaneously induces the expression and activation of proapoptotic and anti-proliferative gene products, including p53, p21 and CASP3 (Choo et al, 2006;Schwartz et al, 2011;Shi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IRF1 mediates anti-proliferative and pro-apoptotic effects in cancer cells in a context-dependent and cell-type-specific manner (Choo et al, 2006). In the absence of antagonistic regulatory factors, increased expression and activation of IRF1 inhibits the expression of pro-survival members of the BCL2 family and simultaneously induces the expression and activation of proapoptotic and anti-proliferative gene products, including p53, p21 and CASP3 (Choo et al, 2006;Schwartz et al, 2011;Shi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of antagonistic regulatory factors, increased expression and activation of IRF1 inhibits the expression of pro-survival members of the BCL2 family and simultaneously induces the expression and activation of proapoptotic and anti-proliferative gene products, including p53, p21 and CASP3 (Choo et al, 2006;Schwartz et al, 2011;Shi et al, 2011). IRF2, an antagonist of IRF1 is known to act as an oncogene product in various types of cancer and when overexpressed in cancer, IRF2 can abolish the tumor suppression function of IRF1 (Choo et al, 2006). Although loss of IRF1 alone is not associated with spontaneous tumor development in mice, it greatly increases tumor susceptibility in combination with loss of other tumor suppressor proteins such as p53 (Nozawa et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tetrac formulation reduced expression of several interferon response pathway genes, e.g., IRF5, but had only a minimally suppressive effect on IRF1. Interferon-regulatory factor 5 (IRF5) protein regulates macrophage contributions to inflammation and IRF1 functions as a tumor suppressor gene (Choo et al, 2006); thus, these tetrac actions have some coherence. Unmodified tetrac and nanotetrac both stimulated expression of SOCS4, the gene product of which is a suppressor of cytokine signaling.…”
Section: Mechanisms Of Anti-inflammatory Properties Of Tetracmentioning
confidence: 99%
“…diseases [40]. Recently, Chapin et al [41] indicated that the expression level of IRF1 was changed in the peripheral blood, which can be used as a marker to reflect the glucocorticoid response.…”
Section: Discussionmentioning
confidence: 99%